Predictive control in matrix converters. Part II, Control strategies, weaknesses and trends - Rivera, Marco; Wheeler, Patrick; Olloqui, A. (2016)
The second part of this paper presents an overview of different control strategies and applications for matrix converters (MCs) where predictive control techniques are applied. It will be shown that predictive control is a promising alternative to control MCs due to its simplicity and flexibility to include different constrains in the con¬trol for different industrial applications such as renewable energies, grid interconnection, multi-drives systems control, among others. In addition, some limitations and weaknesses of predictive control in MCs will be discussed as well as some future trends and applications.